An analysis on how proposed requirements for near zero energy buildings manages PV electricity in combination with two different types of heat pumps and its policy implications – A Swedish example. (February 2017) - Thygesen, Richard; Karlsson, Björn
Abstract: This paper presents an analysis on how exhaust air- and ground source- heat pumps in combination with PV-systems affects the specific energy demand of buildings with the proposed Swedish near zero energy building definition and its policy implications. It also presents a method on how to estimate the contribution from the photovoltaic-system on the reduction of the specific energy demand of the building. A challenge with the proposed near zero energy building definition is that it is not clearly defined how it manages photovoltaic electricity as a mean to reduce the specific energy demand of buildings. The results suggest that the building with the ground source heat pump and heat recovery ventilation has the lowest specific energy demand. The proposed definition will give an advantage to system combinations comprised of heat pumps and PV-systems and this will lead to the possibility to build less insulated buildings with higher heat losses than for a building with a non-electrical heating system. A higher share of heat pumps can lead to lower electricity production in Sweden because of lost heating loads in district heating systems and a higher electricity demand. Highlights: We analyzed how the proposed Swedish NZE building definition manages PV electricity. The building with a GSHP has the lowest specific energy demand. Two different assumptions on the usage of PV electricity was used. The difference between the two assumptions is 6 kWh/m 2 for both the GSHP and EAHP.